2009
DOI: 10.1080/00958970902801493
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and crystal structures of two Schiff-base copper(II) complexes with urease inhibition

Abstract: Two new copper(II) complexes, [CuL1(N 3 )] (1) and [CuL2(NCS, were prepared and structurally characterized by elemental analyses, infrared spectroscopy, and single-crystal X-ray diffraction. Complex 1 is an azide coordinated mononuclear complex, while complex 2 is a terminal thiocyanate coordinated mononuclear complex. The coppers in both complexes are four-coordinate, square-planar. Both complexes show potent urease inhibitory properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…The results indicate that the inhibitory efficiency of the complex towards urease may be influenced by the transition metal and ligands, and the inhibitory activity probably is due to strong Lewis acid properties of copper ions and the ligands strengthen the inhibitory activity of the complexes. The results are in accord with those reported previously, where some Cu(II) complexes have stronger urease inhibitory activities to urease than their parent ligands and metal ion, with IC 50 ranging from 1 to 50 μM [15,28,[35][36][37][38][39]. Compared with the data reported before, the complexes reported in this study exhibit fairly strong inhibitory activity to urease and may be used as urease inhibitors.…”
Section: Resultssupporting
confidence: 95%
“…The results indicate that the inhibitory efficiency of the complex towards urease may be influenced by the transition metal and ligands, and the inhibitory activity probably is due to strong Lewis acid properties of copper ions and the ligands strengthen the inhibitory activity of the complexes. The results are in accord with those reported previously, where some Cu(II) complexes have stronger urease inhibitory activities to urease than their parent ligands and metal ion, with IC 50 ranging from 1 to 50 μM [15,28,[35][36][37][38][39]. Compared with the data reported before, the complexes reported in this study exhibit fairly strong inhibitory activity to urease and may be used as urease inhibitors.…”
Section: Resultssupporting
confidence: 95%
“…It is notable that both complexes possess stronger urease inhibitory properties than the corresponding Schiff bases and the zinc iodide, but weaker than those of the copper(II) complexes we reported previously. [6,22] FIG. 2.…”
Section: Urease Inhibitory Activitiesmentioning
confidence: 96%
“…A recent research indicated that the Schiff base complexes had potent urease inhibitory activity. [6] Zinc complexes with Schiff bases have attracted much attention in coordination chemistry and bioinorganic chemistry due to their versatile structures and interesting biological properties. [7][8][9][10][11][12] …”
Section: Introductionmentioning
confidence: 99%
“…When compared to those we reported previously, it can be concluded that the urease inhibitory activity of zinc complexes is weaker than those of the copper(II) and cobalt(III) complexes. [18][19][20][21] …”
Section: Urease Inhibitory Activitymentioning
confidence: 98%
“…Figures 1 and 2 give perspective views of complexes 1 and 2, respectively. Both complexes crystallize in crystallographic [18] 29.19 ± 0.32 C 13 H 17 Br 3 CuN 2 O [18] 23.63 ± 0.71 C 11 H 13 BrClCuN 5 O [19] 13.0 ± 0.4 C 13 H 16 BrClN 2 O 3 Zn [19] > 100 C 14 H 18 ClCuN 5 O [20] 37.2 ± 0.5 C 14 H 16 ClCuN 3 O 2 S [20] 41.1 ± 0.7 C 53 H 68 Cl 4 Co 2 N 14 O 9 [21] 27.12 ± 0.73 C 14 H 20 Cl 2 N 2 O 3 Zn [21] > 100 HL > 100 Zn(CH 3 COO) 2 > 100 ZnI 2 > 100 Acetohydroxamic acid 45.37 ± 0.31 each other, and are comparable to those reported in the similar Schiff base zinc(II) complexes. [14][15][16] The thiocyanate ligands in 1 are nearly linear and show bent coordination mode with the zinc atoms [N5-C12-S1/Zn1-N5-C12 = 178.8(4) • /173.7(4) • ].…”
Section: Ir Spectramentioning
confidence: 99%